1998
DOI: 10.1007/bf01299769
|View full text |Cite
|
Sign up to set email alerts
|

Pain and discomfort experienced after placement of a conventional or a superelastic NiTi aligning archwire

Abstract: Two nickel-titanium arch-wire types commonly used for initial tooth alignment were compared with regard to the pain/discomfort patients experience during the initial phase of tooth movement. The two arch wires used were a superelastic nickel-titanium alloy, 0.014 inch Sentalloy, Light (GAC International Inc. Central Islip, NY, USA) and a 0.014 inch Nitinol (Unitek, Monrovia, CA, USA), a conventional nickel-titanium aligning archwire. One hundred and twenty-eight consecutive patients attending an orthodontic un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
97
1
19

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(137 citation statements)
references
References 23 publications
20
97
1
19
Order By: Relevance
“…25,26 When compared to other pain/discomfort assessment methods like the verbal rating scales, VAS is more precise and demonstrates better sensitivity between small changes in pain intensity. 27,28 The general time-course of pain intensity concurs with previous studies as the pain level peaked within the first 2 days after archwire insertion, and then gradually declined to near baseline levels 6 to 7 days postoperatively, 4,5,16,17 which indicates that any differences in pain/discomfort are likely to be minimal after 7 days. This observed pain time-course correlates well with the underlying biologic response to orthodontic forces.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…25,26 When compared to other pain/discomfort assessment methods like the verbal rating scales, VAS is more precise and demonstrates better sensitivity between small changes in pain intensity. 27,28 The general time-course of pain intensity concurs with previous studies as the pain level peaked within the first 2 days after archwire insertion, and then gradually declined to near baseline levels 6 to 7 days postoperatively, 4,5,16,17 which indicates that any differences in pain/discomfort are likely to be minimal after 7 days. This observed pain time-course correlates well with the underlying biologic response to orthodontic forces.…”
Section: Discussionsupporting
confidence: 86%
“…18 When comparing conventional Nitinol wires to superelastic Sentalloy wires over 1 week following archwire placement, a significant difference in the overall pain response could not be found. 17 However, Fernandes et al 17 found that conventional Nitinol wires induced significantly higher pain levels than superelastic Sentalloy wires at 4 hours. Similar to our study, Jones and Chan 16 and Fernandes et al 17 used a visual analog scale to evaluate the pain intensity.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, Fernandes et al 17 found that conventional Nitinol wires induced significantly higher pain levels than superelastic Sentalloy wires at 4 hours. Similar to our study, Jones and Chan 16 and Fernandes et al 17 used a visual analog scale to evaluate the pain intensity. VAS is one of the most commonly used tools in the measurement of the perceived discomfort during orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies evaluated the pain intensity experienced by patients during the initial alignment stage of treatment with different archwires. [16][17][18] Bearing these studies in mind, there are no definite conclusions as to which archwire is associated with the least pain. 19 Therefore, the aim of this study was to evaluate the pain experience during the initial aligning phase of orthodontic treatment with three types of NiTi wires: superelastic NiTi, thermoelastic NiTi, and Nitinol aligning archwires.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Pain starts about 4 hours after insertion of the appliance, peaks between 12 hours and 3 days after insertion and then decreases for up to 7 days. [2][3][4][5] Almost all patients (95%) report and suffer pain or discomfort 24 hours after insertion of fixed appliances, and fixed appliances may produce higher pain responses than removable appliances. [6][7][8] Pain scores tend to be higher in anterior than in posterior teeth.…”
Section: Introductionmentioning
confidence: 99%